2013
DOI: 10.1017/s1461145712001186
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine self-administration differentially modulates the expression of endogenous cannabinoid system-related proteins in the hippocampus of Lewis vs. Fischer 344 rats

Abstract: The endocannabinoids anandamide and 2-arachidonyl glycerol (2-AG) are modulators of glutamate and γ-aminobutyric acid (GABA), two transmitters involved in cocaine addiction. However, little is known on the effects of cocaine on the enzymes that produce and degrade endocannabinoids. The present work addresses the effects of cocaine self-administration on the immunohistochemical expression of endocannabinoid signalling (ECS)-related proteins in the hippocampus. The study has been performed on two different strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 72 publications
3
23
0
Order By: Relevance
“…This gene-behavior correlation is also observed in Lewis and Fischer 344 rat strains. For example, Lewis rats display lower PR break points for cocaine self-administration, but have higher CB 2 R expression in hippocampus than those of Fischer 344 rats who display higher PR break points for cocaine self-administration (Rivera et al, 2013), which agrees with our findings in mice and rats. Therefore, quantitative and qualitative changes in the mCB 2 R gene might contribute to differential receptor responses to cocaine self-administration.…”
Section: Discussionsupporting
confidence: 90%
“…This gene-behavior correlation is also observed in Lewis and Fischer 344 rat strains. For example, Lewis rats display lower PR break points for cocaine self-administration, but have higher CB 2 R expression in hippocampus than those of Fischer 344 rats who display higher PR break points for cocaine self-administration (Rivera et al, 2013), which agrees with our findings in mice and rats. Therefore, quantitative and qualitative changes in the mCB 2 R gene might contribute to differential receptor responses to cocaine self-administration.…”
Section: Discussionsupporting
confidence: 90%
“…This finding was associated with enhanced expression of CB1 receptors. In a previous study by our group (Rivera et al, 2013), we demonstrated a similar finding in the Hc of Lewis rats self-administering cocaine. Moreover, we cannot ignore the possibility that the observed changes in NAPE-PLD/FAAH may involve non-CB1-acting endocannabinoids, such as oleoylethanolamide (OEA).…”
Section: Discussionsupporting
confidence: 84%
“…In light of the previously observed differences in the endocannabinoid system between strains [6,5], we investigated the effects of these differences on cannabinoid self-administration. Neither LEW nor F344 rats acquired a stable WIN self-administration behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In light of these results, and given the close relationship between the cannabinoid and opioid systems, we analyzed the levels of endocannabinoid-related proteins in the hippocampus of LEW and F344 rats [5]. LEW rats exhibited weaker CB 1 expression but stronger CB 2 expression than F344 rats.…”
Section: Introductionmentioning
confidence: 99%